Climate change and outbreaks of Southern Pine Beetle Dendroctonus frontalis in Honduras - Rojas, M.R.; Locatelli, Bruno; Billings, R. (2010)
Pine forests, consisting primarily of Pinus oocarpa and P caribaea, cover some 2.5 million hectares and are one of the principal natural resources and a significant foundation for development in Honduras. Historically, these forests have been subjected to ecological impacts and economic losses caused principally by wildfires and, to a lesser but no less significant extent, by the southern pine beetle, Dendroctonus frontalis (Coleoptera, Curculionidae). According to studies conducted in the United States and beliefs of rural Honduran landowners, a relationship exists between the activity of this insect pest and environmental conditions. To explore this relationship, we developed a model relating periodic southern pine beetle outbreaks and environmental conditions in Honduras. We found that increases in mean ambient temperatures in the month of June, reductions in mean monthly precipitation in June and July, and climatic anomalies in warm months that influence the annual frequency of wildfires were correlated with the occurrence and extent of southern pine beetle outbreaks since 1982. With the small amount of information available and lacking previous studies on the causes of bark beetle outbreaks in Central America, this study provides valuable information on the importance of forest management to address southern pine beetle outbreaks and illustrates a general approach that will help to predict the effects of climate change on pine forests of Honduras.